MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA KATOLIK MELALUI METODE NARATIF EKSPERENSIAL DENGAN TEMA YESUS KRISTUS MATERI BERSYUKUR ATAS KARYA KESELAMATAN ALLAH MELALUI TOKOH TOKOH PERJAJIAN LAMA KELAS II SD NEGERI SRONDOL WETAN 06 SEMARANG - F. Setyo Budianto (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2021)
Understanding God's Work of Salvation material for second graders is difficult because the material is abstract. This is evidenced by the low motivation and learning achievement of students, which is only an average of 73. below the KKM score of 75. In order to increase the average learning achievement, a fun learning method is needed so that abstract material can be understood by students. The purpose of this research is to increase motivation and learning achievement by using experiential narrative method. Learning begins by telling various stories, which are taken from personal experience or folklore combined with stories from the Bible related to the material of God's Work of Salvation. This classroom action research was conducted at SD Negeri Srondol Wetan 06 class II, with three cycles and the number of students 3. The research variables were student motivation and achievement. Data obtained through observation and test techniques, and processed by descriptive analysis. The results showed that students' learning motivation increased from 82.5% in the first cycle to 86.8% in the second cycle and 92.25% in the third cycle. While learning achievement also increased from the first cycle the class average of 83.3 to 86.6 and 93.3 in the third cycle. Conclusion: experiential narrative method is proven to increase motivation and average learning achievement. Suggestion: the experiential narrative method can be applied to other subjects that have almost the same characteristics.